2017
DOI: 10.1016/j.fertnstert.2017.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis, especially mild disease: a risk factor for miscarriages

Abstract: NCT02511626.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 66 publications
1
29
0
4
Order By: Relevance
“…This association could be related to a genotoxic effect on the oocyte induced by the iron content in the endometrioma fluid [19]. Schwartz et al reported a higher miscarriage rate in patients with mild endometriosis, as superficial lesions provoke severe inflammation, possibly leading to defective folliculogenesis, fertilization, and/or implantation [27]. A retrospective cohort study thus showed a higher miscarriage rate in all types of endometriosis (superficial, endometrioma, DIE) compared to the healthy controls [28].…”
Section: Discussionmentioning
confidence: 99%
“…This association could be related to a genotoxic effect on the oocyte induced by the iron content in the endometrioma fluid [19]. Schwartz et al reported a higher miscarriage rate in patients with mild endometriosis, as superficial lesions provoke severe inflammation, possibly leading to defective folliculogenesis, fertilization, and/or implantation [27]. A retrospective cohort study thus showed a higher miscarriage rate in all types of endometriosis (superficial, endometrioma, DIE) compared to the healthy controls [28].…”
Section: Discussionmentioning
confidence: 99%
“…The similar findings were achieved by other scientists. In the course of independent studies, they concluded that patients with endometriosisassociated infertility undergoing IVF reflect with a significantly reduced level of all markers of the reproductive function, resulting in a lower pregnancy rate than in the control group [7][8][9][10][11] ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Endometriosis, which is described as the presence of endometrial gland and stroma outside the uterine cavity, is an important women’s health problem seen in 6–10% of women that causes degradation in the quality of life with clinical effects, such as infertility, dysmenorrhea, dyspareunia and chronic pelvic pain 14 . Its pathophysiology has not yet been fully resolved, and an effective treatment for it has not yet been found 5,6 .…”
Section: Introductionmentioning
confidence: 99%